La partitura teatrale nella “svolta concertistica” di Carmelo Bene - Mancini, Leonardo (Mimesis Journal, 2018)
The “musical turn” of Carmelo Bene’s production begun in 1979 and remains little explored. However, it was one of the culminating moments in which the relation between the voice, the music and the listening were pushed to the limit of the “suspension of the tragic” and achieved full realisation. This article examines the earliest of these musical performances by Carmelo Bene: the Manfred originally written by Lord Byron and with musics by Schumann. The essay highlights also intriguing similarities between the use of the voice in Manfred and in the history of the Italian theatre, suggesting a possible confluence of nineteenth century declamatory techniques.